1998
DOI: 10.1128/jvi.72.4.2999-3004.1998
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Enzymatically Active Rabbit Hemorrhagic Disease Virus RNA-Dependent RNA Polymerase in Escherichia coli

Abstract: The rabbit hemorrhagic disease virus (RHDV) (isolate AST/89) RNA-dependent RNA-polymerase (3Dpol) coding region was expressed in Escherichia coli by using a glutathioneS-transferase-based vector, which allowed milligram purification of a homogeneous enzyme with an expected molecular mass of about 58 kDa. The recombinant polypeptide exhibited rifampin- and actinomycin D-resistant, poly(A)-dependent poly(U) polymerase. The enzyme also showed RNA polymerase activity in in vitro reactions with synthetic RHDV subge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Similar snap-back RNA synthesis was observed with the poliovirus RdRp, 3D pol , purified from infected HeLa cells (24,49), and recombinant RdRps of rabbit hemorrhagic disease virus and bovine viral diarrhea virus expressed in E. coli (43,50). RdRps from some animal viruses were able to synthesize template-size products, but only in the presence of an artificial primer (30,32,43). In contrast, RdRps from most of the plant RNA viruses can recognize the structured 3Ј end of plant viral RNA as a promoter and initiate RNA synthesis de novo.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Similar snap-back RNA synthesis was observed with the poliovirus RdRp, 3D pol , purified from infected HeLa cells (24,49), and recombinant RdRps of rabbit hemorrhagic disease virus and bovine viral diarrhea virus expressed in E. coli (43,50). RdRps from some animal viruses were able to synthesize template-size products, but only in the presence of an artificial primer (30,32,43). In contrast, RdRps from most of the plant RNA viruses can recognize the structured 3Ј end of plant viral RNA as a promoter and initiate RNA synthesis de novo.…”
supporting
confidence: 63%
“…A primer-dependent RNA synthesis using a snap-back RNA template is not expected to yield an authentic RNA product, because the 3Ј end of the RNA template will inevitably be excluded from the product, or extra nucleotides will be included in the product. Similar snap-back RNA synthesis was observed with the poliovirus RdRp, 3D pol , purified from infected HeLa cells (24,49), and recombinant RdRps of rabbit hemorrhagic disease virus and bovine viral diarrhea virus expressed in E. coli (43,50). RdRps from some animal viruses were able to synthesize template-size products, but only in the presence of an artificial primer (30,32,43).…”
supporting
confidence: 56%
“…The lack of an effective cell culture system for rabbit caliciviruses [ 2 , 39 ] prompted us to adopt cell-free in vitro assays for testing inhibitors of the RdRp, a protein that represents a prime target for antiviral drug design due to its essential role in the virus replication cycle and the fact that eukaryotic cells do not possess closely related enzymes. Sequence similarities between the 3D RdRp of picornaviruses and the RHDV polyprotein cleavage product p58 suggest that both polypeptides have a similar role in genome replication [ 40 , 41 ]. Expression of the respective coding region in Escherichia coli (E. coli) showed that p58 is indeed an enzymatically active RdRp [ 40 ], and did not demonstrate DNA-dependent RNA polymerase, reverse transcriptase or DNA-dependent DNA polymerase activities [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence similarities between the 3D RdRp of picornaviruses and the RHDV polyprotein cleavage product p58 suggest that both polypeptides have a similar role in genome replication [ 40 , 41 ]. Expression of the respective coding region in Escherichia coli (E. coli) showed that p58 is indeed an enzymatically active RdRp [ 40 ], and did not demonstrate DNA-dependent RNA polymerase, reverse transcriptase or DNA-dependent DNA polymerase activities [ 41 ]. Crystal structure of RHDV RdRp revealed that this enzyme adopts a shape that resembles a right hand, with domains corresponding to the fingers, palm and thumb, as seen in the three-dimensional structures of many other polymerases [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viral RdRp plays a central role in replication of the RNA genome, which is a critical step in the pathogenesis of many RNA viruses. To date, most of the knowledge regarding the biochemical properties of RdRp comes from studies of animal RNA viruses, such as poliovirus (2,4,14), hepatitis C virus (3,23), and rabbit hemorrhagic disease virus (38), and plant viruses, such as brome mosaic virus (17,31,33,35) and tobacco mosaic virus (25). Unlike that of the enzyme from animal viruses, the structural organization of plant viral RdRp is relatively less well characterized.…”
Section: Resultsmentioning
confidence: 99%